Early Prenatal Diagnosis of Double Aortic Arch: Prevalence, Associated Anomalies and Outcome - Zmora, Osnat; Beloosesky, Ron; Khatib, Nizar; Ginsberg, Yuval; Khoury, Asad; Bronshtein, Moshe (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Our aims were to describe the feasibility of diagnosis of DAA in early pregnancy and to assess its prenatal prevalence, associated anomalies and outcome.Materials and Methods A retrospective cohort review of all DAA cases diagnosed by early prenatal transvaginal scans at 12–17 weeks of gestation between the years 2007–2018 was performed. Associated anomalies, genetic abnormalities and long-term postnatal outcome were evaluated.Results 12 cases of DAA were diagnosed by early prenatal transvaginal scans at a median of 15 (range: 12–17) weeks of gestation out of a total of 28 654 early scans preformed with a prevalence of at least 1:2378. Associated anomalies/genetic abnormalities were found in 5/12 (42 %) cases. The diagnosis was confirmed postnatally in all newborns. In two cases termination of pregnancy was performed. Four patients (40 %) were symptomatic. Six patients (60 %) underwent surgery due to symptoms or due to severe obstruction on imaging with resolution of symptoms in all except one patient.Conclusion DAA can be readily diagnosed transvaginally even in the first trimester. Its prevalence is 1:2387. A search for associated anomalies and genetic abnormalities should be performed. If DAA is isolated, the prognosis with or without surgery is usually good.
Keywords: double aortic arch; early prenatal diagnosis; fetal prevalence; outcome